IMPROVEMENT OF DIGITAL IMAGE WITH HISTOGRAM EQUALIZATION METHOD - Muhammad Ullila Fahry; Darlena Darlena (Sean Institute, 2019)
Digital image has become an inherent thing in everyday life. This is supported by the increasingly sophisticated technology of today where communication devices such as mobile phones have been able to use the role of replacing analog cameras to take pictures or even record videos. Capture the moments of happiness or just want to record an event becomes very easy to do, but sometimes the resulting photo is less satisfactory because of the mobile phone's specifications and other factors such as poor lighting (dark). Efforts to improve become very necessary, but because the application to do this only exists on the computer and not too many are found on mobile phones, this becomes difficult to do. One method for image enhancement is the Histogram Equalization method. This method can be used to improve image quality related to lighting by maintaining color constancy. The use of the histogram equalization method is considered easy because of its simplicity and relatively better performance on almost all types of images. The operation of HE (Histogram Equalization) is carried out by remapping the gray level of the image based on the probability distribution of the gray input level. This flattens and dynamically stretches the various histogram images and results in an overall increase in contrast.